Topology optimisation design of multiconstraint continuum structure using sequential quadratic programming method. (31st July 2008) - Yang, S.; Guo, D.M.
Topology optimisation has been extensively studied and successfully applied in engineering community. Present topology optimisation are mainly concentrating on solving optimisation problems with volumetric constraints, while in engineering fields most structures have assembly and stability requirements. In this paper, Topology optimisation model which has compliance minimisation or compliant objective considering stress, volumetric and geometric constraints simultaneously, is proposed. Ways to solve the optimisation problem generated in optimisation process are discussed. SQP method is applied to solve this topology optimisation problem. In the end, two design optimisation problems are presented to show the feasibility of the proposed design approach.